Sex-Specific Routes to Independent Breeding in a Polygynous Cooperative Breeder - Josi, Dario; Flury, Jana M.; Reyes-Contreras, Maria; Tanaka, Hirokazu; Taborsky, Michael; Frommen, Joachim G. (Frontiers in Ecology and Evolution, 2021)
How can individuals obtain a breeding position and what are the benefits associated with philopatry compared to dispersal? These questions are particularly intriguing in polygamous cooperative breeders, where dispersal strategies reflect major life history decisions, and routes to independent breeding may utterly differ between the sexes. We scrutinized sex-dependent life-history routes by investigating dispersal patterns, growth rates and mortality in a wild colony of the cooperatively breeding cichlid Neolamprologus savoryi. Our data reveal that female helpers typically obtain dominant breeding positions immediately after reaching sexual maturity, which is associated with strongly reduced growth. In contrast, males obtain breeder status only at twice the age of females. After reaching sexual maturity, males follow one of two strategies: (i) they may retain their subordinate status within the harem of a dominant male, which may provide protection against predators but involves costs by helping in territory maintenance, defence and brood care; or (ii) they may disperse and adopt a solitary status, which diminishes survival chances and apparently reflects a best-of-a-bad-job strategy, as there are no obvious compensating future fitness benefits associated with this pathway. Our study illustrates that sex-dependent life history strategies strongly relate to specific social structures and mating patterns, with important implications for growth rates, the age at which breeding status is obtained, and survival.